Decreased interleukin(IL)-35 Expression is Associated with Active Intraocular Inflammation in Vogt-Koyanagi-Harada (VKH) Disease. (19th May 2019) - Hu, Jianping; Qin, Yirong; Yi, Shenglan; Wang, Chaokui; Yang, Jinglu; Yang, Lu; Wang, Luoziyi; Kijlstra, Aize; Yang, Peizeng; Li, Hong
ABSTRACT: Purpose : Recent studies have reported that IL-35 has a protective effect in autoimmune disease. In this study, we explored the role of IL-35 in the pathogenesis of Vogt-Koyanagi-Harada (VKH) disease. Methods : The IL-35/EBI3 and IL-35/P35 mRNA level was assayed by Real-Time PCR. The level of IL-35 in serum was detected by ELISA. PBMCs and monocyte-derived DCs were cultured with or without IL-35 and the concentration of IL-17, IL-10, IFN-γ, IL-6, TNF-α, and IL-1β in supernatants was tested by ELISA. Results : The serum level of IL-35 is reduced in active VKH patients. The mRNA expression of the two subunits IL-35/EBI3 and IL-35/P35 in PBMCs from patients with active VKH was also decreased. IL-35 significantly inhibited IFN-γ and IL-17 expression and induced IL-10 production by PBMCs and inhibited IL-6 production by monocyte-derived DCs. Conclusion : The current study suggests that a decreased IL-35 expression may be involved in the pathogenesis of VKH disease.